Veins of Deception: An Intriguing Case of Extradural Spinal AVF Mimicking Longitudinal Extensive Transverse Myelitis - Ujjwal Agarwal; Vipul Gupta; Pallav Bhatter; D. S. Rao; Rajsrinivas Parthasarathy (Journal of Clinical Interventional Radiology ISVIR)
Longitudinally extensive transverse myelitis (LETM) is a rapidly progressing demyelinating disease affecting the spinal cord over three or more vertebral segments. Acquired central nervous system demyelinating diseases such as multiple sclerosis, neuromyelitis optica, systemic autoimmune causes, infections, and post-vaccination are common reasons; the majority is idiopathic. Vascular disorders of the spinal cord potentially can cause long segment spinal involvement mimicking LETM. Spinal dural arteriovenous fistulas represent approximately 70% of all spinal vascular malformations. Spinal extradural arteriovenous fistulas (AVFs) are relatively uncommon vascular disorders also mimicking LETM. Here, we present a very rare case of extradural spinal AVF mimicking LETM.